The Poet, the Lion, Talking Pictures, El Farolito, a Wedding in St. Roch, the Big Box Store, the Warp in the Mirror, Spring, Midnights, Fire & All - Wright, C. D., 1949-2016 (Copper Canyon Press, 2016)
"A companion to her astonishing collection of prose Cooling Time, C.D. Wright argues for poetry as a way of being and seeing"--